Diagnostic accuracy of tuberculosis screening tests in a prospective multinational cohort: chest radiography with computer-aided detection, xpert tuberculosis host response, and C-Reactive protein - Crowder, Rebecca; Thangakunam, Balamugesh; Andama, Alfred; Christopher, Devasahayam J.; Dalay, Victoria; Nwamba, Welile; Kik, Sandra; Nguyen, Dong Van; Nguyen, Nhung Viet; Phillips, Patrick P. J.; Ruhwald, Morten; Theron, Grant; et al. (Clinical infectious diseases, 2024)
Background Accessible, accurate screening tests are necessary to advance tuberculosis case finding and early detection in high-burden countries.Methods We prospectively screened adults with >= 2 weeks of cough at primary health centers in the Philippines, Vietnam, South Africa, Uganda, and India. Participants underwent chest radiography, Cepheid Xpert TB Host Response (Xpert HR) testing, and point-of-care C-reactive protein (CRP) testing (Boditech). Chest radiographs were processed using CAD4TB v7, a computer-aided detection (CAD) algorithm. We assessed diagnostic accuracy against a microbiologic reference standard (sputum Xpert Ultra, culture). Optimal cutoff points were chosen to maximize specificity at 90% sensitivity. Two-test screening algorithms were considered, using (1) sequential negative serial screening (with positive defined as positive on either test) and (2) sequential positive serial screening (with positive defined as positive on both tests).Results Between July 2021 and August 2022, a total of 1392 participants with presumptive tuberculosis had valid index tests and reference standard results, and 303 (22%) had confirmed tuberculosis. In head-to-head comparisons, CAD4TB v7 showed the highest specificity at 90% sensitivity (70.3% vs 65.1% for Xpert HR [95% confidence interval for absolute difference in specificity, 1.6%-8.9%] and vs 49.7% for CRP [17.0%-24.3%]). Three 2-test screening algorithms met World Health Organization target product profile minimum accuracy thresholds and had higher accuracy than any test alone. At 90% sensitivity, the specificity was 79.6% for Xpert HR-CAD4TB (sequential negative), 75.9% for CRP-CAD4TB (sequential negative), and 73.7% for Xpert HR-CAD4TB (sequential positive).Conclusions CAD4TB achieves target product profile targets and outperforms Xpert HR and CRP. Combining screening tests further increased accuracy. Clinical Trials Registration. NCT04923958Conclusions CAD4TB achieves target product profile targets and outperforms Xpert HR and CRP. Combining screening tests further increased accuracy. Clinical Trials Registration. NCT04923958 Our study compares the diagnostic accuracy of 3 available tuberculosis screening tests (chest radiograph processed with CAD4TB, Xpert TB Host Response, and C-reactive protein) among people with presumptive tuberculosis in 5 countries (Uganda, South Africa, Philippines, Vietnam, and India).
Gesehen am 13.01.2026